THE CONCEPT OF LINGUACULTUROLOGY AND LINGUACULTURAL COMPETENCE. - Saniyazova, S. (EurasianUnionScientists, 2021)
This article examines the concepts of linguoculturology and linguocultural competence as well as their importance in the education system. Linguocultural competence is presented as an obligatory area of knowledge in the system of philological education.